Spatial ability and 3D model colour-coding affect anatomy performance: a cross-sectional and randomized trial - Koh, Ming Yi (2023)
Photorealistic 3D models (PR3DM) have great potential to supplement anatomy education; however, there is evidence that realism can increase cognitive load and negatively impact anatomy learning, particularly in students with decreased spatial ability. These differing viewpoints have resulted in difficulty in incorporating PR3DM when designing anatomy courses. To determine the effects of spatial ability on anatomy learning and reported intrinsic cognitive load using a drawing assessment, and of PR3DM versus an Artistic colour-coded 3D model (A3DM) on extraneous cognitive load and learning performance. First-year medical students participated in a cross-sectional (Study 1) and a double-blind randomised control trial (Study 2). Pre-tests analysed participants' knowledge of anatomy of the heart (Study 1, N = 50) and liver (Study 2, N = 46). In Study 1, subjects were first divided equally using a mental rotations test (MRT) into low and high spatial ability groups. Participants memorised a 2D-labeled heart valve diagram and sketched it rotated 180°, before self-reporting their intrinsic cognitive load (ICL). For Study 2, participants studied a liver PR3DM or its corresponding A3DM with texture-homogenisation, followed by a liver anatomy post-test, and reported extraneous cognitive load (ECL). All participants reported no prior anatomy experience. Participants with low spatial ability (N = 25) had significantly lower heart drawing scores (p = 0.001) than those with high spatial ability (N = 25), despite no significant differences in reported ICL (p = 0.110). Males had significantly higher MRT scores than females (p = 0.011). Participants who studied the liver A3DM (N = 22) had significantly higher post-test scores than those who studied the liver PR3DM (N = 24) (p = 0.042), despite no significant differences in reported ECL (p = 0.720). This investigation demonstrated that increased spatial ability and colour-coding of 3D models are associated with improved anatomy performance without significant increase in cognitive load. The findings are important and provide useful insight into the influence of spatial ability and photorealistic and artistic 3D models on anatomy education, and their applicability to instructional and assessment design in anatomy.